2015
DOI: 10.1007/s40684-015-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Green manufacturing: Relationship between adoption of green operational practices and green performance of brazilian ISO 9001-certified firms

Abstract: The present work aims at analyzing how the adoption of a proactive environmental management via green operational practices (GOPs) correlates to the Green Performance (GrP) of a given set of ISO 9001-certified firms in Brazil. To this end, we elaborated a conceptual framework about environmental management, GOPs, and GrP. Such theoretical foundation supported the development of empirical research through quantitative analysis. For the analysis, 75 questionnaires were collected from ISO 9001 certified companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A study undertaken by Soubihia et al (2015) among Brazilian ISO 9001-certified firms revealed that GMP in terms of adopting green operational practices is a positive and significant precursor of firm's green performance. Kalyar et al (2019) further found that GMP, as a dimension of green supply chain management (GSCM), has a significant direct effect on the EP.…”
Section: Green Manufacturing and Firm Reputationmentioning
confidence: 99%
“…A study undertaken by Soubihia et al (2015) among Brazilian ISO 9001-certified firms revealed that GMP in terms of adopting green operational practices is a positive and significant precursor of firm's green performance. Kalyar et al (2019) further found that GMP, as a dimension of green supply chain management (GSCM), has a significant direct effect on the EP.…”
Section: Green Manufacturing and Firm Reputationmentioning
confidence: 99%
“…The main finding from the study is that profit is the best predictor of SMEs financial performance, pollution prevention and control is positively and significantly related to profit and recycling is negatively and significantly related to profit. 2015) Soubihia et al (2015) analyze how the adoption of a proactive environmental management via green operational practices correlates to the green performance of SMEs. Tomsic et al ( ) Tomsic et al (2015 attempt to analyze the link between corporate sustainability and economic performance.…”
Section: Jansson Et Al (2015)mentioning
confidence: 99%
“…The relevance of considering environmental aspects in the business context can be easily found in the current literature. Commitment to the environment has become a key variable in the contemporary competitive scenario (Molina-Azorin et al, 2015;Soubihia et al, 2015). Companies recognize the fact that environmental sustainability has implications for their competitive positions (Godinho Filho & Ganga, 2016).…”
Section: Introductionmentioning
confidence: 99%